2018
DOI: 10.1039/c8ra08894b
|View full text |Cite
|
Sign up to set email alerts
|

Triterpenoids with α-glucosidase inhibitory activity and cytotoxic activity from the leaves ofAkebia trifoliata

Abstract: Ten pentacyclic triterpenoids including a new multiflorane triterpene acid, 2α,3β,23-trihydroxymultiflor-7-en-28-oic acid (1), and a new lupane triterpene monoglucoside named akebiaoside C (2), were obtained from the leaves ofAkebia trifoliata.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 17 publications
(28 reference statements)
0
13
0
Order By: Relevance
“…However, only 38.30% of patients with grade III acne had an excellent response, 5% had a moderate response and 56.66% had a good response. There were no significant adverse effects in all the patients who received the medications Gopal et al ( 2001 ), Jiang et al ( 2019 ), Feng et al ( 2020 ) Akebonoic acid Triterpenoids Akebia trifoliata 9.0 ND 409 (acarbose) ND ND ND Jeong et al ( 2007 ), Sánchez-González et al ( 2014 ),; Yuan et al ( 2015 ), Ouyang et al ( 2018 ) …”
Section: Plant Secondary Metabolites As Alpha-glucosidase Inhibitorsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, only 38.30% of patients with grade III acne had an excellent response, 5% had a moderate response and 56.66% had a good response. There were no significant adverse effects in all the patients who received the medications Gopal et al ( 2001 ), Jiang et al ( 2019 ), Feng et al ( 2020 ) Akebonoic acid Triterpenoids Akebia trifoliata 9.0 ND 409 (acarbose) ND ND ND Jeong et al ( 2007 ), Sánchez-González et al ( 2014 ),; Yuan et al ( 2015 ), Ouyang et al ( 2018 ) …”
Section: Plant Secondary Metabolites As Alpha-glucosidase Inhibitorsmentioning
confidence: 97%
“…Interestingly, despite being structuraly very similar, triterpenoids isolated from Akebia trifoliata (compounds 80–88; online resource 1 and 2) showed a broad variation in the reported IC 50 against alpha-glucosidase (9–592 µM) (Ouyang et al 2018 ). While compounds 83 and 84 showed comparable IC 50 values and low inhibitory activity, the structurally similar compound gypsogenic acid (87) exhibited significantly higher inhibition that can be attribituted to the presence of a carboxy group at positions 23.…”
Section: Plant Secondary Metabolites As Alpha-glucosidase Inhibitorsmentioning
confidence: 99%
“…Although the biological activities of compounds 14 and 17 have not been described yet, compound 15 was reported to exhibit anti-HIV-1 protease activity [ 37 ], antibacterial activity [ 38 ], an inhibitory effect on Aβ42-induced fibrillogenesis [ 39 ], an α-glucosidase inhibitory effect, and moderate in vitro cytotoxic activity against human cancer cell lines [ 40 ]. Compound 15 has been isolated mostly from the flowering plant family Lardizabalaceae, such as Stauntonia obovatifoliola , Akebia quinata , and Akebia trifoliata [ 37 , 38 , 39 , 40 ]. Compound 16 , which was previously isolated from the Colombian climbing plant Boussingaultia baselloides , was found to exhibit hypoglycemic activity in rats [ 41 ].…”
Section: Oleanane Triterpenoid Saponinsmentioning
confidence: 99%
“…In this research, T 1 – T 3 possessed excellent activity with an IC 50 value 42.1±5.4, 19.6±3.2, and 11.2±2.3 μM in parallel with the standard drug acarbose (IC 50 =106.3±8.2 μM), whose α‐glucosidase inhibitory effect was approximately 2, 5 and 9‐fold stronger than acarbose, respectively. As shown in Table 1, the T 1 – T 3 inhibitory effects of α‐glucosidase are weaker than those previously reported [29,30] . These results indicated that the T 1 – T 3 in the stems of A. trifoliata were significant α‐glucosidase inhibitors and had great prospects as effective and safe hypoglycemic agents for diabetes control.…”
Section: Resultsmentioning
confidence: 68%